A Comprehensive Study on Anticancer Activity of Tridax procumbens Leaf Extracts on A549 and Hep G2 Cell Lines - Pittu Vishnu Priya; A. V. S. S. S. Gupta; A. Srinivasa Rao (Challenges and Advances in Pharmaceutical Research Vol. 10, 2022)
Cancer is a disease which is severely effecting the global human population. There is always a constant demand for new therapies to treat and prevent this life-threatening disease. Scientific and research interest is drawing its attention towards naturally derived compounds, as they are considered to have less toxic side effects compared to current treatments such as chemotherapy, radiation etc. Medicinal plant Tridax procumbens produces naturally occurring secondary metabolites which is being investigated for the anticancer activities against A549 (human lung cancer cell line), Hep G2 (human liver carcinoma cell line) leading to the development of new clinical drug. MTT and trypan blue dye exclusion assays were used to assess the anticancer activity of T.procumbens ethanol, acetone, and aqueous leaf extracts on selected human cancerous cell lines. The MTT assay relies on the ability of viable cells’ mitochondrial enzymes to convert the yellow soluble salt MTT to the purple blue insoluble formazan precipitate, which is then quantified spectrophotometrically at 570 nm. The Trypan blue assay relies on cell staining. Cells are then counted under a microscope using a hemocytometer, and non-viable cells are stained blue while viable cells remain unstained. The aqueous leaf extract of T. procumbens has not shown any anticancer activity. However, acetone and ethanol leaf extracts of T. procumbens has shown potent anticancer activity on A549 (human lung cancer cell line), Hep G2 (human liver carcinoma cell line). T. procumbens investigated for anticancer potential by MTT assay and trypan blue exclusion assay. The acetone and ethanol leaf extracts of T. procumbens have shown potent anticancer activity on selected human cell lines.